Digitization protocol for scoring reproductive phenology from herbarium specimens of seed plants. (28th February 2018) - Yost, Jennifer M.; Sweeney, Patrick W.; Gilbert, Ed; Nelson, Gil; Guralnick, Robert; Gallinat, Amanda S.; Ellwood, Elizabeth R.; Rossington, Natalie; Willis, Charles G.; Blum, Stanley D.; Walls, Ramona L.; Haston, Elspeth M.; et al.
Abstract : Premise of the Study: Herbarium specimens provide a robust record of historical plant phenology (the timing of seasonal events such as flowering or fruiting). However, the difficulty of aggregating phenological data from specimens arises from a lack of standardized scoring methods and definitions for phenological states across the collections community. Methods and Results: To address this problem, we report on a consensus reached by an iDigBio working group of curators, researchers, and data standards experts regarding an efficient scoring protocol and a data‐sharing protocol for reproductive traits available from herbarium specimens of seed plants. The phenological data sets generated can be shared via Darwin Core Archives using the Extended MeasurementOrFact extension. Conclusions: Our hope is that curators and others interested in collecting phenological trait data from specimens will use the recommendations presented here in current and future scoring efforts. New tools for scoring specimens are reviewed.